Marketing research with telephone surveys: is it time to change? - Vicente, P.; Reis, E. (Journal of Global Marketing, 2010)
Telephone surveys have been an important mode for collecting primary data in the marketing field in recent decades.However, the scenario of telephone coverage is changing mainly due to a massive increase in mobile phone-only usage, which can put the quality of telephone survey estimates at risk. The advance of mobile phones as the preferred telecommunication is a global phenomenon occurring in every country, although at varying speeds. This article examines the relationship between telephone coverage and the coverage bias of telephone survey estimates in the current scenario of telephone coverage across European countries. Findings reveal that the capacity for fixed-line telephonebased sampling frames to represent the overall adult population is becoming critical, especially in countries with declining fixed-line-telephone penetration rates